Lanthanum-doped tin-based negative electrode material and preparation method and application thereof
The lanthanum doped tin-based negative electrode material is prepared by mixing the acid-treated carbon source, tin-containing compounds and lanthanum-containing compounds, which solves the problem of volume expansion of the tin-based negative electrode material during charging and discharging, and improves the structural stability and electrochemical properties of the material.
Patent Information
- Application Number
- CN202311397825.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-25
- Publication Date
- 2025-04-25
AI Technical Summary
Tin-based negative electrode materials are prone to severe volume expansion during the charging and discharging of lithium-ion batteries, causing the electrode materials to disintegrate and fall off, affecting the specific capacity, cycle stability and safety performance of the battery.
The lanthanum doped tin-based anode material was prepared by mixing the acid-treated carbon source, the tin-containing compound and the lanthanum-containing compound evenly in anhydrous ethanol. The method includes drying treatment and heating the material under an inert atmosphere to improve the structural stability and electrochemical properties of the material.
This method effectively reduces the volume expansion of the tin-based anode material during charging and discharging, improves the mechanical stability and conductivity of the material, and enhances the electrochemical performance and life of lithium-ion batteries.
Smart Images

Figure CN119873879A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a lanthanum-doped tin-based negative electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion battery is a secondary battery (rechargeable battery) that mainly relies on the movement of lithium ions between the positive and negative electrodes to work. + The lithium-ion battery has the advantages of high voltage, small size, light weight, high specific energy, no memory effect, no pollution, low self-discharge, and long life. In recent years, it has become a research hotspot and has achieved rapid development. The performance of lithium-ion batteries depends largely on the performance of their negative electrode materials.
[0003] Tin-based negative electrode materials have become one of the hot topics in the research of negative electrode materials for lithium-ion batteries due to their advantages such as high theoretical capacity, good safety and abundant sources. However, tin-based negative electrode materials are often accompanied by severe volume expansion during the actual charging and discharging process, which causes the disintegration and shedding of electrode materials, thus affecting the specific capacity, cycle stability and safety performance of the battery.
[0004] Therefore, there is an urgent need to modify tin-based negative electrode materials to improve their performance. Summary of the invention
[0005] The purpose of the present invention is to provide a lanthanum-doped tin-based negative electrode material and a preparation method and application thereof in view of the defects existing in the prior art. The preparation method can improve the volume expansion of the tin-based negative electrode material during the charging and discharging process and the structural stability of the tin-based negative electrode material, thereby improving the electrochemical performance of the tin-based negative electrode material.
[0006] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a lanthanum-doped tin-based negative electrode material, the preparation method comprising:
[0007] The acid-treated carbon source, the tin-containing compound, and the lanthanum-containing compound are added to anhydrous ethanol and mixed evenly to obtain a mixed solution; wherein the molar ratio of carbon element, tin element, and lanthanum element is 150:(1-10):(0.1-5);
[0008] Drying the mixed solution to obtain a lanthanum-doped tin-based negative electrode material precursor;
[0009] Under an inert atmosphere, the lanthanum-doped tin-based negative electrode material precursor is placed in a tube furnace for heating to obtain the lanthanum-doped tin-based negative electrode material.
[0010] Preferably, before adding the acid-treated carbon source, the tin-containing compound, and the lanthanum-containing compound to the anhydrous ethanol, the method further comprises acid-treating the carbon source; wherein the acid treatment is specifically:
[0011] The carbon source raw material is added to the acidic solution according to a certain solid-liquid ratio, and then placed in a constant temperature oil bath for condensation and reflux, and then centrifuged to obtain the carbon source powder; wherein the solid-liquid ratio is 1:50-1:150;
[0012] The carbon source powder is washed and dried to obtain the acid-treated carbon source.
[0013] Further preferably, the carbon source includes one or more of carbon nanotubes, graphene, natural graphite or artificial graphite; and the acidic solution includes one or more of concentrated nitric acid, concentrated hydrochloric acid or concentrated sulfuric acid.
[0014] Further preferably, the centrifugal rotation speed is 5000 rpm-8000 rpm, and the time is 8 minutes-12 minutes.
[0015] Preferably, the tin-containing compound includes one or more of stannous chloride, tin tetrachloride, stannous chloride hydrate or tin tetrachloride hydrate; the lanthanum-containing compound includes one or more of lanthanum nitrate, lanthanum sulfate, lanthanum chloride, lanthanum oxide or lanthanum fluoride.
[0016] Preferably, the drying process is specifically:
[0017] The mixed solution is spray dried; wherein the rotation speed of the spray drying equipment is 15000 rpm-25000 rpm, the air inlet temperature is 140-180°C, and the air outlet temperature is 80°C-100°C.
[0018] Preferably, the heating specifically comprises:
[0019] The temperature is raised from room temperature to 600°C-1000°C at a heating rate of 2°C / min-6°C / min, and kept at this temperature for 2 hours-8 hours.
[0020] In a second aspect, the present invention provides a lanthanum-doped tin-based negative electrode material, wherein the lanthanum-doped tin-based negative electrode material is prepared by any preparation method described in the first aspect above.
[0021] In a third aspect, the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the lanthanum-doped tin-based negative electrode material described in the second aspect.
[0022] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode sheet described in the third aspect.
[0023] The present invention provides a method for preparing a lanthanum-doped tin-based negative electrode material. The preparation method combines a tin-containing compound, a lanthanum-containing compound and a carbon source. On the one hand, the carbon source can absorb part of the stress caused by expansion, reducing the stress transmitted to the tin-based battery material. At the same time, it also acts as a supporting material in the negative electrode material, which can enhance the mechanical stability of the negative electrode material. The carbon source can improve the conductivity of the battery, which helps to distribute the charge more evenly, reduce the formation of hot spots, and thus reduce the heat concentration caused by volume expansion. In short, the addition of the carbon source makes the formed lanthanum-doped tin-based negative electrode material have a more stable lithium insertion and tin removal framework, improves the mechanical stability and conductivity of the battery, and reduces the volume expansion during charging and discharging. It can help to slow down the volume expansion of the battery material and improve the performance and life of the battery. On the other hand, an alloy system is formed by doping with metal lanthanum, so that the prepared material has better metal ductility and improves the stability of the material structure, thereby effectively improving the electrochemical properties of the first coulombic efficiency and rate performance of the tin-based negative electrode material. In short, the preparation method provided by the embodiment of the present invention is simple to operate, easy to control, safe and efficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Flow chart of the method for preparing lanthanum-doped tin-based negative electrode material provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0027] The embodiment of the present invention provides a method for preparing a lanthanum-doped tin-based negative electrode material, the process of which is as follows: Figure 1 As shown, the following steps are included:
[0028] Step 110, adding the acid-treated carbon source, the tin-containing compound, and the lanthanum-containing compound into anhydrous ethanol, and mixing them evenly to obtain a mixed solution;
[0029] The molar ratio of carbon, tin and lanthanum is 150:(1-10):(0.1-5). The tin-containing compound may include one or more of stannous chloride, tin tetrachloride, stannous chloride hydrate or tin tetrachloride hydrate. The lanthanum-containing compound may include one or more of lanthanum nitrate, lanthanum sulfate, lanthanum chloride, lanthanum oxide or lanthanum fluoride. The mixing method may be ultrasonic oscillation for 2 hours.
[0030] Before executing step 110, the preparation method further includes acid treatment of the carbon source to remove impurities and oxides on the surface of the material. The specific process is as follows:
[0031] Firstly, the carbon source raw material is added into the acidic solution according to a certain solid-liquid ratio, then placed in a constant temperature oil bath for condensation reflux, and then centrifuged to obtain the carbon source powder.
[0032] Specifically, the solid-liquid ratio may be 1:50-1:150. The acidic solution may specifically include one or more of concentrated nitric acid, concentrated hydrochloric acid or concentrated sulfuric acid. Among them, the concentration of concentrated nitric acid is not less than 8 mol / L; the concentrated hydrochloric acid may specifically be hydrochloric acid with a mass fraction of hydrogen chloride exceeding 20%; the concentrated sulfuric acid may specifically be a sulfuric acid aqueous solution with a mass fraction greater than or equal to 70%.
[0033] The temperature of the constant temperature oil bath pot is specifically 90°C-130°C, and the condensation reflux time can be specifically 10 hours-12 hours. Condensation reflux in the constant temperature oil bath pot can separate the impurities and oxides removed by acidification to obtain a separated solution. Afterwards, the separated solution is centrifuged in a high-speed centrifuge for solid-liquid separation to obtain a carbon source powder. The centrifugal speed is specifically 5000 rpm-8000 rpm, and the time can be 8-12 minutes, preferably 10 minutes.
[0034] Secondly, the carbon source powder is washed and dried to obtain an acid-treated carbon source.
[0035] The washing may be performed multiple times with deionized water and then multiple times with ethanol. The drying may be performed in an oven at a temperature of 80° C. The carbon source may include one or more of carbon nanotubes, graphene, natural graphite or artificial graphite.
[0036] Step 120, drying the mixed solution to obtain a lanthanum-doped tin-based negative electrode material precursor;
[0037] Specifically, the mixed solution is spray dried. The rotation speed of the spray drying equipment is 15000 rpm-25000 rpm. The air inlet temperature can be specifically 140-180°C, and the air outlet temperature can be specifically 80°C-100°C.
[0038] Step 130 , placing the lanthanum-doped tin-based negative electrode material precursor in a tube furnace for heating under an inert atmosphere to obtain the lanthanum-doped tin-based negative electrode material.
[0039] Specifically, the inert atmosphere may be nitrogen or argon. The heating process is specifically to increase the temperature from room temperature to 600°C-1000°C at a heating rate of 2°C / min-6°C / min, and keep the temperature for 2 hours-8 hours.
[0040] In this process, the tin-containing compound, the lanthanum-containing compound and the carbon source are compounded, and the tin-containing compound, the lanthanum-containing compound and the carbon source are compounded. On the one hand, the carbon source can absorb part of the stress caused by the expansion, reducing the stress transmitted to the tin-based battery material, and also acts as a supporting material in the negative electrode material, which can enhance the mechanical stability of the negative electrode material, and the carbon source can improve the conductivity of the battery, which helps to distribute the charge more evenly, reduce the formation of hot spots, and thus reduce the heat concentration caused by volume expansion. In short, the addition of the carbon source makes the formed lanthanum-doped tin-based negative electrode material have a more stable lithium insertion and tin removal framework, improves the mechanical stability and conductivity of the battery, and reduces the volume expansion during the charge and discharge process. It can help to slow down the volume expansion of the battery material and improve the performance and life of the battery. On the other hand, an alloy system is formed by doping with metallic lanthanum, so that the prepared material has better metal ductility, improves the stability of the material structure, and effectively improves the electrochemical properties of the first coulomb efficiency and rate performance of the tin-based negative electrode material. In short, the preparation method provided by the embodiment of the present invention is simple to operate, easy to control, safe and efficient.
[0041] The lanthanum-doped tin-based negative electrode material provided by the embodiment of the present invention can be applied to the electrode material of lithium-ion batteries.
[0042] In order to better understand the technical solution provided by the present invention, the following uses a number of specific examples to illustrate the specific process of preparing lanthanum-doped tin-based negative electrode materials using the method provided in the above embodiment of the present invention, as well as the electrochemical properties of the prepared lanthanum-doped tin-based negative electrode materials.
[0043] Example 1
[0044] In the first step, the carbon source is treated with acid.
[0045] At a solid-liquid ratio of 1:150, weigh 100g of carbon nanotube raw material and place it in a flask, and slowly add 15000mL of concentrated nitric acid to the flask. Place the flask in a 100°C constant temperature oil bath for condensation reflux treatment for 10 hours, and then separate the solid and liquid by high-speed centrifugation at a centrifugal speed of 8000 rpm for 10 minutes to obtain carbon nanotube powder. Then wash the carbon nanotube powder three times with deionized water, and then wash it three times with ethanol, and then place it in an oven at 80°C for 8 hours to obtain acid-treated carbon nanotubes.
[0046] In the second step, 50 g of carbon nanotubes, 40 g of stannous chloride and 20 g of lanthanum nitrate were weighed, added into 300 mL of anhydrous ethanol, ultrasonically vibrated for 2 hours, and mixed evenly to obtain a mixed solution.
[0047] The third step is to spray dry the mixed solution. The air inlet temperature of the spray drying equipment is 180°C, the air outlet temperature is 100°C, and the rotation speed is 25,000 rpm to obtain a lanthanum-doped tin-based negative electrode material precursor.
[0048] In the fourth step, under a nitrogen atmosphere, the lanthanum-doped tin-based negative electrode material precursor is placed in a tubular furnace, and the temperature is increased at a heating rate of 2°C / min so that the tubular furnace is heated from room temperature to 1000°C, and kept at 1000°C for 2 hours to obtain a lanthanum-doped tin-based negative electrode material.
[0049] The prepared lanthanum-doped tin-based negative electrode material was used as the negative electrode material of the lithium-ion battery, and button-type half-cells were assembled for testing. The specific process is as follows:
[0050] Firstly, the obtained lanthanum-doped tin-based negative electrode material, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber are added to deionized water in a mass ratio of 93%:2%:2%:3%, mixed evenly with a beater, coated on a copper foil, and dried in a vacuum oven at 80°C for 10 hours to obtain a dried electrode.
[0051] Afterwards, the dried electrode sheet is cut into 12 mm discs as the negative electrode sheet of the lithium-ion battery.
[0052] Then, the button-type lithium-ion half-cell is assembled using the negative electrode sheet. The aqueous electrolyte of the assembled button-type lithium-ion half-cell is 1 mol / L lithium hexafluorophosphate (Li PF6), and the solvent of the electrolyte is ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC), wherein the volume ratio of EC, DMC and DEC is 1:1:1. The counter electrode is a lithium sheet.
[0053] Finally, electrochemical tests were performed to evaluate its electrochemical performance.
[0054] The electrochemical test mode is: the first week 0.1C discharge to 0.005V, 0.05C discharge to 0.005V, 0.02C discharge to 0.005V, stand for 5s and charge to 1V at 0.1C. The test conditions of subsequent cycles are: 0.1C current density, 0.05V-1V voltage.
[0055] The discharge in the above electrochemical test is a lithium insertion process, corresponding to the charge in the full battery, and the charge in the above electrochemical test is a lithium removal process, corresponding to the discharge of the full battery.
[0056] Example 2
[0057] In the first step, the carbon source is treated with acid.
[0058] At a solid-liquid ratio of 1:100, weigh 100g of carbon nanotube raw material and place it in a flask, and slowly add 10000mL of concentrated nitric acid to the flask. Place the flask in a constant temperature oil bath at 90°C for condensation reflux treatment for 12 hours, and then separate the solid and liquid by high-speed centrifugation at a centrifugal speed of 5000 rpm for 12 minutes to obtain carbon nanotube powder. Then wash the carbon nanotube powder three times with deionized water, and then wash it three times with ethanol, and then place it in an oven at 80°C for 8 hours to obtain acid-treated carbon nanotubes.
[0059] In the second step, 50 g of carbon nanotubes, 20 g of stannous chloride and 20 g of lanthanum sulfate were weighed, added into 300 mL of anhydrous ethanol, ultrasonically vibrated for 2 hours, and mixed evenly to obtain a mixed solution.
[0060] The third step is to spray dry the mixed solution, the air inlet temperature of the spray drying equipment is 140°C, the air outlet temperature is 80°C, and the rotation speed is 25,000 rpm to obtain a lanthanum-doped tin-based negative electrode material precursor.
[0061] In the fourth step, under a nitrogen atmosphere, the lanthanum-doped tin-based negative electrode material precursor is placed in a tubular furnace, and the temperature is increased at a heating rate of 10°C / min so that the tubular furnace is heated from room temperature to 600°C, and kept at 600°C for 8 hours to obtain a lanthanum-doped tin-based negative electrode material.
[0062] Afterwards, the prepared lanthanum-doped tin-based negative electrode material was used as the negative electrode material of a lithium-ion battery, and button-type half-cells were assembled for testing. The specific assembly and testing process was the same as in Example 1.
[0063] Example 3
[0064] In the first step, the carbon source is treated with acid.
[0065] At a solid-liquid ratio of 1:50, weigh 100g of carbon nanotube raw material and place it in a flask, and slowly add 5000mL of concentrated sulfuric acid to the flask. Place the flask in a 130°C constant temperature oil bath for condensation reflux treatment for 10 hours, and then separate the solid and liquid by high-speed centrifugation at a centrifugal speed of 8000 rpm for 10 minutes to obtain carbon nanotube powder. Then wash the carbon nanotube powder three times with deionized water, and then wash it three times with ethanol, and then place it in an oven at 80°C for 8 hours to obtain acid-treated carbon nanotubes.
[0066] In the second step, 50 g of carbon nanotubes, 40 g of stannous chloride and 20 g of lanthanum nitrate were weighed, added into 300 mL of anhydrous ethanol, ultrasonically vibrated for 2 hours, and mixed evenly to obtain a mixed solution.
[0067] The third step is to spray dry the mixed solution, the air inlet temperature of the spray drying equipment is 160°C, the air outlet temperature is 90°C, and the rotation speed is 15,000 rpm to obtain a lanthanum-doped tin-based negative electrode material precursor.
[0068] In the fourth step, under a nitrogen atmosphere, the lanthanum-doped tin-based negative electrode material precursor is placed in a tubular furnace, and the temperature is increased at a heating rate of 5°C / min so that the tubular furnace is heated from room temperature to 800°C, and kept at 800°C for 4 hours to obtain a lanthanum-doped tin-based negative electrode material.
[0069] Afterwards, the prepared lanthanum-doped tin-based negative electrode material was used as the negative electrode material of a lithium-ion battery, and a button-type half-cell was assembled for testing. The specific assembly and testing process was the same as in Example 1.
[0070] Example 4
[0071] In the first step, the carbon source is treated with acid.
[0072] At a solid-liquid ratio of 1:80, weigh 100g of carbon nanotube raw material and place it in a flask, and slowly add 8000mL of concentrated sulfuric acid to the flask. Place the flask in a constant temperature oil bath at 110°C for condensation reflux treatment for 11 hours, and then separate the solid and liquid by high-speed centrifugation at a centrifugal speed of 8000 rpm for 10 minutes to obtain carbon nanotube powder. Then wash the carbon nanotube powder three times with deionized water, and then wash it three times with ethanol, and then place it in an oven at 80°C for 8 hours to obtain acid-treated carbon nanotubes.
[0073] In the second step, 50 g of carbon nanotubes, 15 g of stannous chloride and 15 g of lanthanum nitrate were weighed, added into 300 mL of anhydrous ethanol, ultrasonically vibrated for 2 hours, and mixed evenly to obtain a mixed solution.
[0074] The third step is to spray dry the mixed solution, the air inlet temperature of the spray drying equipment is 170°C, the air outlet temperature is 100°C, and the rotation speed is 20,000 rpm to obtain a lanthanum-doped tin-based negative electrode material precursor.
[0075] In the fourth step, under a nitrogen atmosphere, the lanthanum-doped tin-based negative electrode material precursor is placed in a tubular furnace, and the temperature is increased at a heating rate of 4°C / min so that the tubular furnace is heated from room temperature to 750°C, and kept at 750°C for 5 hours to obtain a lanthanum-doped tin-based negative electrode material.
[0076] Afterwards, the prepared lanthanum-doped tin-based negative electrode material was used as the negative electrode material of a lithium-ion battery, and a button-type half-cell was assembled for testing. The specific assembly and testing process was the same as in Example 1.
[0077] Example 5
[0078] In the first step, the carbon source is treated with acid.
[0079] At a solid-liquid ratio of 1:140, 100g of graphene raw material was weighed and placed in a flask, and 14000mL of concentrated sulfuric acid was slowly added to the flask. The flask was placed in a constant temperature oil bath at 130°C for condensation reflux treatment for 10 hours, and then subjected to high-speed centrifugal solid-liquid separation at a centrifugal speed of 8000 rpm for 10 minutes to obtain graphene powder. The graphene powder was then washed three times with deionized water, and then washed three times with ethanol, and then placed in an oven at 80°C for 8 hours to obtain acid-treated graphene.
[0080] In the second step, 50 g of graphene, 25 g of tin tetrachloride and 10 g of lanthanum chloride were weighed, added into 300 mL of anhydrous ethanol, ultrasonically vibrated for 2 hours, and mixed evenly to obtain a mixed solution.
[0081] The third step is to spray dry the mixed solution, the air inlet temperature of the spray drying equipment is 165°C, the air outlet temperature is 85°C, and the rotation speed is 22,000 rpm to obtain a lanthanum-doped tin-based negative electrode material precursor.
[0082] The fourth step is to place the lanthanum-doped tin-based negative electrode material precursor in a tubular furnace under an argon atmosphere, heat it at a heating rate of 5°C / min, so that the tubular furnace is heated from room temperature to 850°C, and keep it at 850°C for 4 hours to obtain the lanthanum-doped tin-based negative electrode material.
[0083] Afterwards, the prepared lanthanum-doped tin-based negative electrode material was used as the negative electrode material of a lithium-ion battery, and a button-type half-cell was assembled for testing. The specific assembly and testing process was the same as in Example 1.
[0084] Example 6
[0085] In the first step, the carbon source is treated with acid.
[0086] At a solid-liquid ratio of 1:135, 100g of graphene raw material was weighed and placed in a flask, and 13500mL of concentrated hydrochloric acid was slowly added to the flask. The flask was placed in a constant temperature oil bath at 110°C for condensation reflux treatment for 11 hours, and then subjected to high-speed centrifugal solid-liquid separation at a centrifugal speed of 6000 rpm for 10 minutes to obtain graphene powder. The graphene powder was then washed three times with deionized water, and then washed three times with ethanol, and then placed in an oven at 80°C for 8 hours to obtain acid-treated graphene.
[0087] In the second step, 50 g of graphene, 30 g of tin tetrachloride and 20 g of lanthanum fluoride were weighed, added into 300 mL of anhydrous ethanol, ultrasonically vibrated for 2 hours, and mixed evenly to obtain a mixed solution.
[0088] The third step is to spray dry the mixed solution. The air inlet temperature of the spray drying equipment is 175°C, the air outlet temperature is 100°C, and the rotation speed is 21,000 rpm to obtain a lanthanum-doped tin-based negative electrode material precursor.
[0089] The fourth step is to place the lanthanum-doped tin-based negative electrode material precursor in a tubular furnace under an argon atmosphere, heat it at a heating rate of 2°C / min, so that the tubular furnace is heated from room temperature to 950°C, and keep it at 950°C for 6 hours to obtain the lanthanum-doped tin-based negative electrode material.
[0090] Afterwards, the prepared lanthanum-doped tin-based negative electrode material was used as the negative electrode material of a lithium-ion battery, and button-type half-cells were assembled for testing. The specific assembly and testing process was the same as in Example 1.
[0091] Example 7
[0092] In the first step, the carbon source is treated with acid.
[0093] At a solid-liquid ratio of 1:125, 100g of graphene raw material was weighed and placed in a flask, and 12500mL of concentrated hydrochloric acid was slowly added to the flask. The flask was placed in a constant temperature oil bath at 105°C for condensation reflux treatment for 12 hours, and then subjected to high-speed centrifugal solid-liquid separation at a centrifugal speed of 7500 rpm for 10 minutes to obtain graphene powder. The graphene powder was then washed three times with deionized water, and then washed three times with ethanol, and then placed in an oven at 80°C for 8 hours to obtain acid-treated graphene.
[0094] In the second step, 50 g of graphene, 22.5 g of tin tetrachloride and 12.5 g of lanthanum oxide were weighed, added into 300 mL of anhydrous ethanol, ultrasonically vibrated for 2 hours, and mixed evenly to obtain a mixed solution.
[0095] The third step is to spray dry the mixed solution, the air inlet temperature of the spray drying equipment is 175°C, the air outlet temperature is 95°C, and the rotation speed is 20,000 rpm to obtain a lanthanum-doped tin-based negative electrode material precursor.
[0096] The fourth step is to place the lanthanum-doped tin-based negative electrode material precursor in a tubular furnace under an argon atmosphere, heat it at a heating rate of 5°C / min, so that the tubular furnace is heated from room temperature to 1000°C, and keep it at 1000°C for 3 hours to obtain the lanthanum-doped tin-based negative electrode material.
[0097] Afterwards, the prepared lanthanum-doped tin-based negative electrode material was used as the negative electrode material of a lithium-ion battery, and button-type half-cells were assembled for testing. The specific assembly and testing process was the same as in Example 1.
[0098] Example 8
[0099] In the first step, the carbon source is treated with acid.
[0100] At a solid-liquid ratio of 1:80, weigh 100g of graphene raw material and place it in a flask, and slowly add 8000mL of concentrated hydrochloric acid to the flask. Place the flask in a constant temperature oil bath at 95°C for condensation reflux treatment for 12 hours, and then separate the solid and liquid by high-speed centrifugation at a centrifugal speed of 5500 rpm for 9 minutes to obtain graphene powder. Then wash the graphene powder three times with deionized water, then wash it three times with ethanol, and place it in an oven at 80°C for 8 hours to obtain acid-treated graphene.
[0101] In the second step, 50 g of graphene, 30 g of tin tetrachloride and 20 g of lanthanum oxide were weighed, added into 300 mL of anhydrous ethanol, ultrasonically vibrated for 2 hours, and mixed evenly to obtain a mixed solution.
[0102] The third step is to spray dry the mixed solution, the air inlet temperature of the spray drying equipment is 155°C, the air outlet temperature is 85°C, and the rotation speed is 19000 rpm to obtain a lanthanum-doped tin-based negative electrode material precursor.
[0103] In the fourth step, under an argon atmosphere, the lanthanum-doped tin-based negative electrode material precursor is placed in a tubular furnace, and the temperature is increased at a heating rate of 5°C / min so that the tubular furnace is heated from room temperature to 900°C, and kept at 900°C for 6 hours to obtain a lanthanum-doped tin-based negative electrode material.
[0104] Afterwards, the prepared lanthanum-doped tin-based negative electrode material was used as the negative electrode material of a lithium-ion battery, and button-type half-cells were assembled for testing. The specific assembly and testing process was the same as in Example 1.
[0105] Example 9
[0106] In the first step, the carbon source is treated with acid.
[0107] At a solid-liquid ratio of 1:140, 100g of natural graphite raw material was weighed and placed in a flask, and 14000mL of concentrated sulfuric acid was slowly added to the flask. The flask was placed in a constant temperature oil bath at 105°C for condensation reflux treatment for 11 hours, and then subjected to high-speed centrifugal solid-liquid separation at a centrifugal speed of 5000 rpm for 10 minutes to obtain natural graphite powder. The natural graphite powder was then washed three times with deionized water, and then washed three times with ethanol, and then placed in an oven at 80°C for drying for 8 hours to obtain natural graphite after acid treatment.
[0108] In the second step, 50 g of natural graphite, 40 g of tin tetrachloride and 17.5 g of lanthanum fluoride were weighed, added into 300 mL of anhydrous ethanol, ultrasonically vibrated for 2 hours, and mixed evenly to obtain a mixed solution.
[0109] The third step is to spray dry the mixed solution, the air inlet temperature of the spray drying equipment is 180°C, the air outlet temperature is 100°C, and the rotation speed is 17500 rpm to obtain a lanthanum-doped tin-based negative electrode material precursor.
[0110] In the fourth step, under an argon atmosphere, the lanthanum-doped tin-based negative electrode material precursor is placed in a tubular furnace, and the temperature is increased at a heating rate of 2°C / min so that the tubular furnace is heated from room temperature to 800°C, and kept at 800°C for 5.5 hours to obtain a lanthanum-doped tin-based negative electrode material.
[0111] Afterwards, the prepared lanthanum-doped tin-based negative electrode material was used as the negative electrode material of a lithium-ion battery, and button-type half-cells were assembled for testing. The specific assembly and testing process was the same as in Example 1.
[0112] Example 10
[0113] In the first step, the carbon source is treated with acid.
[0114] At a solid-liquid ratio of 1:60, 100g of natural graphite raw material was weighed and placed in a flask, and 6000mL of concentrated sulfuric acid was slowly added to the flask. The flask was placed in a constant temperature oil bath at 95°C for condensation reflux treatment for 12 hours, and then subjected to high-speed centrifugal solid-liquid separation at a centrifugal speed of 8000 rpm for 8 minutes to obtain natural graphite powder. The natural graphite powder was then washed three times with deionized water, and then washed three times with ethanol, and then placed in an oven at 80°C for drying for 8 hours to obtain natural graphite after acid treatment.
[0115] In the second step, 50 g of natural graphite, 35 g of tin tetrachloride and 20 g of lanthanum fluoride were weighed, added into 300 mL of anhydrous ethanol, ultrasonically vibrated for 2 hours, and mixed evenly to obtain a mixed solution.
[0116] The third step is to spray dry the mixed solution, the air inlet temperature of the spray drying equipment is 180°C, the air outlet temperature is 90°C, and the rotation speed is 20,000 rpm to obtain a lanthanum-doped tin-based negative electrode material precursor.
[0117] In the fourth step, under a nitrogen atmosphere, the lanthanum-doped tin-based negative electrode material precursor is placed in a tubular furnace, and the temperature is increased at a heating rate of 3°C / min so that the tubular furnace is heated from room temperature to 750°C, and kept at 750°C for 7 hours to obtain a lanthanum-doped tin-based negative electrode material.
[0118] Afterwards, the prepared lanthanum-doped tin-based negative electrode material was used as the negative electrode material of a lithium-ion battery, and a button-type half-cell was assembled for testing. The specific assembly and testing process was the same as in Example 1.
[0119] Comparative Example 1
[0120] In the first step, the carbon source is treated with acid.
[0121] At a solid-liquid ratio of 1:150, weigh 100g of carbon nanotube raw material and place it in a flask, and slowly add 15000mL of concentrated nitric acid to the flask. Place the flask in a 100°C constant temperature oil bath for condensation reflux treatment for 10 hours, and then separate the solid and liquid by high-speed centrifugation at a centrifugal speed of 8000 rpm for 10 minutes to obtain carbon nanotube powder. Then wash the carbon nanotube powder three times with deionized water, and then wash it three times with ethanol, and then place it in an oven at 80°C for 8 hours to obtain acid-treated carbon nanotubes.
[0122] In the second step, 50 g of carbon nanotubes and 40 g of stannous chloride were weighed, added into 300 mL of anhydrous ethanol, ultrasonically vibrated for 2 hours, and mixed evenly to obtain a mixed solution.
[0123] The third step is to spray dry the mixed solution, the air inlet temperature of the spray drying equipment is 180°C, the air outlet temperature is 100°C, and the rotation speed is 25,000 rpm to obtain a tin-based negative electrode material precursor.
[0124] In the fourth step, under a nitrogen atmosphere, the tin-based negative electrode material precursor is placed in a tubular furnace, and the temperature is increased at a heating rate of 2°C / min so that the tubular furnace is heated from room temperature to 1000°C, and kept at 1000°C for 2 hours to obtain a tin-based negative electrode material.
[0125] Afterwards, the prepared tin-based negative electrode material was used as the negative electrode material of the lithium-ion battery, and button-type half-cells were assembled for testing. The specific assembly and testing process was the same as in Example 1, except that the lanthanum-doped tin-based negative electrode material was replaced with a tin-based negative electrode material.
[0126] Comparative Example 2
[0127] In the first step, 50 g of stannous chloride was weighed, added into 300 mL of anhydrous ethanol, ultrasonically vibrated for 2 hours, and mixed evenly to obtain a mixed solution.
[0128] The third step is to spray dry the mixed solution, the air inlet temperature of the spray drying equipment is 180°C, the air outlet temperature is 100°C, and the rotation speed is 25,000 rpm to obtain a tin-based negative electrode material precursor.
[0129] In the fourth step, under a nitrogen atmosphere, the tin-based negative electrode material precursor is placed in a tubular furnace, and the temperature is increased at a heating rate of 2°C / min so that the tubular furnace is heated from room temperature to 1000°C, and kept at 1000°C for 2 hours to obtain a tin-based negative electrode material.
[0130] Afterwards, the prepared tin-based negative electrode material was used as the negative electrode material of the lithium-ion battery, and button-type half-cells were assembled for testing. The specific assembly and testing process was the same as in Example 1, except that the lanthanum-doped tin-based negative electrode material was replaced with a tin-based negative electrode material.
[0131] Table 1 shows the electrochemical performance test data of the negative electrode materials prepared in the above Examples 1-10 and Comparative Examples 1-2.
[0132] First week coulomb efficiency 100-cycle capacity retention rate Example 1 85.1% 85% Example 2 85.0% 84% Example 3 84.9% 85% Example 4 84.6% 84% Example 5 84.4% 84% Example 6 84.6% 83% Example 7 84.2% 84% Example 8 83.8% 83% Example 9 83.1% 82% Example 10 82.8% 83% Comparative Example 1 76.0% 74% Comparative Example 2 70.5% 58%
[0133] Table 1
[0134] It can be seen from the test data in Table 1 that the first week coulombic efficiency and cycle capacity retention rate of Examples 1-10 are higher than those of Comparative Examples 1 and 2. This is because in the preparation method of a lanthanum-doped tin-based negative electrode material provided in the embodiment of the present invention, the tin-containing compound and the lanthanum-containing compound are respectively compounded with a carbon source, and the conductivity of the carbon source, the absorption of expansion stress and the characteristics of stabilizing the battery structure are utilized to provide a more stable lithium insertion and tin removal framework for the lanthanum-doped tin-based negative electrode material, which plays a good volume buffering role, effectively inhibits the volume expansion of the negative electrode material during the actual charge and discharge process, and reduces the probability of disintegration and shedding of the electrode material. In addition, an alloy system can be formed by doping with metallic lanthanum, so that the prepared negative electrode material has better metal ductility and improves the stability of the negative electrode material structure. Therefore, the lanthanum-doped tin-based negative electrode material provided by the present invention has excellent electrochemical performance, ideal first coulombic efficiency and cycle stability, and has broad application prospects.
[0135] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a lanthanum-doped tin-based negative electrode material, characterized in that: The preparation method comprises: The acid-treated carbon source, the tin-containing compound, and the lanthanum-containing compound are added to anhydrous ethanol and mixed evenly to obtain a mixed solution; wherein the molar ratio of carbon element, tin element, and lanthanum element is 150:(1-10):(0.1-5); Drying the mixed solution to obtain a lanthanum-doped tin-based negative electrode material precursor; Under an inert atmosphere, the lanthanum-doped tin-based negative electrode material precursor is placed in a tube furnace for heating to obtain the lanthanum-doped tin-based negative electrode material.
2. The preparation method according to claim 1, characterized in that: Before adding the acid-treated carbon source, the tin-containing compound, and the lanthanum-containing compound into the anhydrous ethanol, the method further comprises subjecting the carbon source to acid treatment; wherein the acid treatment is specifically: The carbon source raw material is added to the acidic solution according to a certain solid-liquid ratio, and then placed in a constant temperature oil bath for condensation and reflux, and then centrifuged to obtain the carbon source powder; wherein the solid-liquid ratio is 1:50-1:150; The carbon source powder is washed and dried to obtain the acid-treated carbon source.
3. The preparation method according to claim 2, characterized in that: The carbon source includes one or more of carbon nanotubes, graphene, natural graphite or artificial graphite; the acidic solution includes one or more of concentrated nitric acid, concentrated hydrochloric acid or concentrated sulfuric acid.
4. The preparation method according to claim 2, characterized in that: The centrifugal speed is 5000 rpm-8000 rpm, and the time is 8 minutes-12 minutes.
5. The preparation method according to claim 1, characterized in that: The tin-containing compound includes one or more of stannous chloride, tin tetrachloride, stannous chloride hydrate or tin tetrachloride hydrate; the lanthanum-containing compound includes one or more of lanthanum nitrate, lanthanum sulfate, lanthanum chloride, lanthanum oxide or lanthanum fluoride.
6. The preparation method according to claim 1, characterized in that: The drying process is specifically as follows: The mixed solution is spray dried; wherein the rotation speed of the spray drying equipment is 15000 rpm-25000 rpm, the air inlet temperature is 140-180°C, and the air outlet temperature is 80°C-100°C.
7. The preparation method according to claim 1, characterized in that: The heating specifically comprises: The temperature is raised from room temperature to 600°C-1000°C at a heating rate of 2°C / min-6°C / min, and kept at this temperature for 2 hours-8 hours.
8. A lanthanum-doped tin-based negative electrode material, characterized in that: The lanthanum-doped tin-based negative electrode material is prepared by the preparation method described in any one of claims 1 to 7 above.
9. A negative electrode plate, characterized in that: The negative electrode plate comprises the lanthanum-doped tin-based negative electrode material according to claim 8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet according to claim 9.